A Conceptual Design and Numerical Analysis for a Small-Scale and Low-Cost Plastic Recycling Machine - Le Anh T. M.; Doan Hoang D.; Ngo Loc P.; Huynh Ly T.; Huynh Tuan N.; Phan Huy T.; Tran Thanh T. (E3S Web of Conferences, 2019)
A new conceptual design for a small-scale and low-cost plastic recycling machine is generated by combining melting part and compression process. Starting with one of the outstanding requirements is in terms of an affordable-priced machine that can perform two processes with high accuracy and capacity, some issues related to balancing among quality, capacity and cost of machine occurred during a discussion. After implementing various designing methods such as Quality Function Deployment, Reverse Engineering, Morphological Matrix and Pugh Method, an idea of final concept about using an electric oven and hydraulic system to melt down and compress plastic tile which has a dimension of 300x300x9 mm was created. The design of concept is divided into two parts which are mechanical and electrical systems. In a mechanical section, the technical drawing and simulation are made to see how machine performs under operation. Besides, we examined the forces that applied in the moulds to evaluate the strength of the system. In heating and electricity section, we chose electrical components, designed oven parameters and conducted the heating simulation on the mould. In addition, the heating and cooling time was calculated based on the principles of thermodynamics and heat transfer. Furthermore, the manufacturing plan is created to estimate the essential resources producing a certain number of heat-forming machines. In general, the machine needs to be prototyped for controlling its main function and finding practical issues. After that, some improvements could be made to enhance efficiency and increase capacity by designing an optimal mould to more heat absorb and reduce post process, calculate and design more efficient oven, create faster lock mechanism and other improvements for an automatizing machine.